Pengaruh Beban Kerja Terhadap Kinerja Tenaga Kesehatan di Puskesmas Kutalimbaru - Salianto Salianto; Nur Afini Turnip; Jihan Nabila Ritonga; Azzahra Khairani Siregar; Amanda Aqiilah; Lisca Amalia Putri Br Sinaga; Az- Zahra Sabrina Nasution (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The performance of medical personnel is a very vital element in determining the quality of health services at community health centers. Unbalanced workload can affect the capability of medical personnel in carrying out their duties and responsibilities, thereby impacting the quality of service. The aim of this research is to distribute the impact of workload on the performance of medical personnel at the Kutalimbaru Community Health Center. The method used in this research is a quantitative approach with a descriptive survey design which was carried out in May 2026. The population studied included all 20 medical personnel at the Kutalimbaru Community Health Center. The sample was determined using a total sampling technique so that the entire population became respondents. Data was collected using a questionnaire and analyzed descriptively and by simple linear regression. The findings from this study reveal that workload has a significant influence on the performance of health workers with a significance value.